(4x + 1) ² = (3x - 7 )²
equação do 2° grau
Soluções para a tarefa
Respondido por
14
(4x+1) . (4x+1) = (3x-7) .( 3x-7)
16x² + 4x + 4x +1 = 9x² - 21x - 21x + 49
16x² +4x+4x+1 - 9x² +21x +21x -49=0
7x² +50x -48=0
Agora é só fazer baskara
16x² + 4x + 4x +1 = 9x² - 21x - 21x + 49
16x² +4x+4x+1 - 9x² +21x +21x -49=0
7x² +50x -48=0
Agora é só fazer baskara
Perguntas interessantes
Química,
11 meses atrás
Português,
11 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Inglês,
1 ano atrás